Strategies to Enhance Local Government Finance in Nigeria - Ugoh, Samuel; ISINKAYE, Kehinde Abiodun; Ukpere, Wilfred (Annals of Spiru Haret University. Economic Series, 2022)
This study adopted historical approach to political research and used secondary sources of information. This paper focuses on assessing financial challenges facing local governments in Nigeria. The study observed that insufficient allocation from the federation account, lack of effective revenue generation drive, mismanagement of funds, intrusion of the state government into local governments use of funds, amongst others are the major challenges confronting local governments. Nevertheless, if right strategies such as effective planning, accountability, transparency, curbing of financial mismanagement, sound business undertaking, increased fund allocation from federation account are adopted, local Government may be in better position to accelerate the pace of infrastructural development in Nigeria.